Thermal behavior and fluid dynamics within molten pool during laser inside additive manufacturing of 316L stainless steel coating on inner surface of steel tube. (June 2021) - Shi, Xinyu; Gu, Dongdong; Li, Yanze; Dai, Donghua; Ge, Qing; Sun, Yixuan; Chen, Hongyu
Highlights: A novel technology, laser inside additive manufacturing, was studied. A curved substrate was applied to the thermodynamic model. The influence of laser power on the molten pool evolution was studied. The curved surface inducing limit to the spread of the melt was discussed. Abstract: In this study, a transient mesoscale model of the laser inside additive manufacturing (LIAM) has been proposed by the finite volume method (FVM) to investigate the evolution of molten pool morphology. The phase transition, curved substrate topography, the variation of thermo-physical properties, and interfacial forces were considered. The thermal behavior and fluid dynamics within the molten pool during the LIAM of 316L stainless steel coating on the A2 steel tube-substrate were analyzed by a numerical approach. The results reveal that the melt flow driven by temperature gradient promotes the heat and mass transfer in the width direction and limits the heat transfer in the depth direction. By comparing the cases with and without considering fluid dynamics, one can observe that melt flow entails a larger size in width and a smaller size in length to the molten pool. Laser power plays a significant role in the size of the molten pool. With the increase of the laser power from 1000 W to 1400 W, the melt's velocity within the molten pool increases, which promotes the heat and mass transfer effect. A larger molten pool is the consequence. Additionally, the variation of laser power significantly affects the fluid dynamics of heat and mass transfer. Thus, the depth to width ratio first decreases and then shows an increasing trend. Meanwhile, the melt spreading in the length direction of the molten pool were restricted by the curved configuration of the substrate, yielding a restricted movement of the melt and a limited wettability of the molten pool. This study provides an insight into the thermal behavior and fluid dynamics within the molten pool during LIAM. It shows a high potential for a science-based strategy for high-quality inner surface processing.